Mechanical and Thermal Properties of ABS/PMMA/Potassium Titanate Whisker Composites. Issue 4 (4th March 2017) - Zhang, Aimin; Zhao, Guoqun; Hui, Yang; Guan, Yanjin
ABSTRACT: Two kinds of potassium titanate whiskers were filled into ABS (Acrylonitrile-Butadiene-Styrene)/PMMA (Polymethyl Methacrylate) which is often used in rapid heat cycle molding process. The aspect ratio of potassium titanate whiskers 2 is larger than that of potassium titanate whiskers 1. Properties of ABS/PMMA/potassium titanate whiskers composites prepared in a corotating twin-screw extruder were analyzed. The results show that potassium titanate whiskers can improve thermal stability of composites while they cause toughness of composites reduced. Tensile strength of composites increases slightly with 5 wt% potassium titanate whiskers. Halpin–Tsai model can calculate the modulus of composites more accurately. Potassium titanate whiskers 2 is beneficial to the thermal stability of composites, while it makes the viscosity of composites increasing. GRAPHICAL ABSTRACT: